KONSEP TRANSMEDIA STORYTELLING PADA IKLAN CETAK MOBIL VOLKSWAGEN DENGAN MEDIA AUGMENTED REALITY - Ardhariksa Zukhruf Kurniullah (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
New media or convergence, in a few years we often hear, especially the convergence of media that are often associated with new media that is now developing, particularly media-related technology development. The rapidly of media convergence growthto advances in technology these days, especially when the advent of the Internet and the digitization of information. This media convergence brings together the name "three-C" (computing, communication, and content). Once of product a media convergence is transmediaa, in the paradigm of Transmedia, no longer known specific profession. Eg profession as creators of the film, director, screenwriter, animator, producer of the TV program, game creators, content developers, comic artist, broadcaster, author, novelist even journalists. Everything sublimate into a new capacity, the Story Teller. Selection of the research issue at Volkswagon simulation of interactive digital advertising is a new study in the field of advertising in Indonesia, especially on the concept of transmedia storytelling approach to advertising and media convergence. This study use qualitative research approach. While research method used in this research is the method of observation with descriptive type. Data collection techniques in this study using advertising document observation that in this case the advertisement print of Volkswagen Augmented Reality and literature studies / literature. From the results of research conducted can be obtained conclusion that the power of Transmedia Storytelling on this Volkwagon print reinforces a story. The impact is that consumers will be more emotionally attached to the main products and variants and derivatives. The concept of transmedia storytelling advertising can be effective in the process of imaging and delivery of advertising messages, so that the audience can engage fully in augmented reality.. Keywords: convergence, transmedia,storytelling, digital, augmented reality